USING CHESSBOARD TECHNIQUE IN RESPONDING TO THE SHORT STORY TO DEVELOP STUDENTS’ SPEAKING SKILL - Putu Karolina (Universitas Bengkulu, 2016)
This study aimed to answer whether using chessboard technique in responding to short story develops student’s speaking skill or not. The method used in this study was one of the quasi-experimental designs: pretest-posttest non-equivalent comparison control group design. The population of the study was the eleventh-grade student at SMA N 12Palembang and the sample were taken from the population by using purposive sampling. The data were collected by using two instruments, test and questionnaire. The test wasgiven twice to the experimental and control group, as the pretest and the posttest. Thequestionnaire was distributed to the experimental group after conducting the treatment to get more information related to the problem of the study. To verify the hypothesis, thedata from pretest and posttest on the experimental and control group were analyzed byusing paired sample t-test and independent sample t-test. The result of the study showed that applying chessboard technique in responding to the short story develops student’s speaking skills. Some students (60%) in the experimental group achieve good category compared to only a few students (20%) in control group.